Investigation of Self-Efficacy Levels of Football Referees - Mustafa Kayıhan Erbaş; Çağatay Dereceli; Hüseyin Ünlü (Sakarya University Journal of Education)
Inthis study, we aimed to examine the self-efficacy levels of soccer referees inthe context of some demographic variables (gender, education level, age ofstarting refereeing, and ocupation). The study group consisted of a total of154 soccer referees during the 2017-2018 football season of whom 33 (21.4%)were females and 121 (78.6%) were males from different regions andclassifications ( age = 26.87±1.966). The personal information formand the Referee Self-Efficacy Scale (REFS) were used as data collection tools.In the analysis of the data, descriptive statistics were used to identifyself-efficacy levels and to identify demographic variables. In order to compareself-efficacy levels in respect to arithmetic means gender and age selfefficacy scores, independent t-test was used and one-way analysis of variance(ANOVA) was used to compare self-efficacy levels of education level andoccupations. The Tukey’s multiple comparison test was used to determinedifferences between groups. The results revealed that the referees'self-efficacy levels were high and there were significant differences inself-efficacy levels in terms of gender and educational status. Thus, it isrecommended that higher education level be prioritized during the refereeselection and promotion and that experience and physical competence beincreased to elevate the self-efficacy levels of female referees.